Evidence of persistence ofPrevotellaspp. in the cystic fibrosis lung. Issue 6 (June 2017) - Gilpin, D. F.; Nixon, K. A.; Bull, M.; McGrath, S. J.; Sherrard, L.; Rolain, J. M.; Mahenthiralingam, E.; Elborn, J. S.; Tunney, M. M.
Abstract : Purpose. : Prevotella spp. represent a diverse genus of bacteria, frequently identified by both culture and molecular methods in the lungs of patients with chronic respiratory infection. However, their role in the pathogenesis of chronic lung infection is unclear; therefore, a more complete understanding of their molecular epidemiology is required. Methodology. : Pulsed Field Gel Electrophoresis (PFGE) and Random Amplified Polymorphic DNA (RAPD) assays were developed and used to determine the degree of similarity between sequential isolates ( n =42) from cystic fibrosis (CF) patients during periods of clinical stability and exacerbation. Results. : A wide diversity of PFGE and RAPD banding patterns were observed, demonstrating considerable within‐genus heterogeneity. In 8/12 (66.7%) cases, where the same species was identified at sequential time points, pre‐ and post‐antibiotic treatment of an exacerbation, PFGE/RAPD profiles were highly similar or identical. Congruence was observed between PFGE and RAPD (adjusted Rand coefficient, 0.200; adjusted Wallace RAPD‐>PFGE 0.459, PFGE‐>RAPD 0.128). Furthermore, some isolates could not be adequately assigned a species name on the basis of 16S rRNA analysis: these isolates had identical PFGE/RAPD profiles to Prevotella histicola . Conclusion. : The similarity in PFGE and RAPD banding patterns observed in sequential CF Prevotella isolates may be indicative of the persistence of this genus in the CF lung. Further work is required to determine the clinical significance of this finding, and to more accurately distinguish differences in pathogenicity between species.